The Standard Electrical Dictionary : A Popular Dictionary of Words and Terms Used in the Practice of Electrical Engineering - Sloane, T. O'Conor (Thomas O'Conor), 1851-1940 (Salt Lake City, UT : Project Gutenberg, 2008)
"The Standard Electrical Dictionary" by T. O'Conor Sloane is a scientific publication written in the late 19th century. This work serves as a comprehensive reference for terminology related to electrical engineering, providing concise definitions and explanations for a multitude of concepts, terms, and inventions within the field. It reflects the advancements in electrical science, illustrating the context of its era just before significant discoveries like the electron and the development of quantum theory. The opening of this dictionary includes transcriber's notes that acknowledge the corrections of errors and the challenges of maintaining contemporary relevance given the rapidly evolving nature of electrical science. Sloane's preface outlines the purpose of the dictionary as a practical tool aimed at a growing audience interested in the intricacies of electricity, while also addressing the limitations caused by the vastness of the subject matter. The text sets a foundational tone for readers, encouraging them to utilize the indexes and synonyms to navigate through the extensive terminologies to locate and understand the complexities of electrical engineering effectively. (This is an automatically generated summary.)
Release date is 2008-09-05
Produced by Don Kostuch
Keywords: Electricity -- Dictionaries